2022
DOI: 10.11591/eei.v11i3.3778
|View full text |Cite
|
Sign up to set email alerts
|

FPGA-based experimental board for error control codes

Abstract: This paper proposed an experimental device that emulates and facilitates teaching the theoretical concepts of error-control coding (ECC) techniques. Two prototypes laboratory boards were designed and implemented. The first board simulates the transmitter side of a typical digital communication system. It mainly contains a data source, (7,4) Hamming encoder, cyclic redundancy check encoder (CRC), and Gaussian noise generator. The second board has two types of Hamming decoders, a syndrome decoder, and a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Recent research works have shown a growing interest in RF budget analysis and FPGA implementation of mm-wave supported transceivers with CS and DTCWT for wireless communication systems. Researchers [15] and [16] designed and implemented an FPGA-based mm-wave transceiver for 5G mobile communications. They utilized CS to reduce the number of samples needed to retrieve the transmitted signal, resulting in lower computing complexity and hardware requirements.…”
Section: Literature Surveymentioning
confidence: 99%
“…Recent research works have shown a growing interest in RF budget analysis and FPGA implementation of mm-wave supported transceivers with CS and DTCWT for wireless communication systems. Researchers [15] and [16] designed and implemented an FPGA-based mm-wave transceiver for 5G mobile communications. They utilized CS to reduce the number of samples needed to retrieve the transmitted signal, resulting in lower computing complexity and hardware requirements.…”
Section: Literature Surveymentioning
confidence: 99%
“…2149 ratio (k/n) is called the code rate. Dealing with this code as a non-binary error correcting code over galois field (GF) (2 𝑚 ), then this RS code can correct up to [18], [19].…”
Section: Noise Reduction In Plc 31 Impulsive Noise Mitigation Using R...mentioning
confidence: 99%